DNA‐Coated Upconversion Nanoparticles for Sensitive Nucleic Acid FRET Biosensing. (1st May 2022) - Francés‐Soriano, Laura; Estebanez, Nestor; Pérez‐Prieto, Julia; Hildebrandt, Niko
Abstract: Despite the significant advancements of developing upconversion nanoparticles (UCNPs) for high performance biosensing and bioimaging, the development of DNA‐functionalized UCNPs with thin coatings, efficient surface passivation, and fully functional DNAs for hybridization sensing in biological media remains extremely challenging. Here, a straightforward concept of labeling DNA to a thin polysulfonate polymer layer on UCNPs is presented. Both UCNPs and DNA preserve their full functionality as demonstrated by Förster resonance energy transfer (FRET) hybridization assays with a Cy3‐conjugated complementary DNA. The important bioanalytical benefits of the UCNP‐DNA nanohybrids are demonstrated by their implementation into rapid and wash‐free microRNA hybridization FRET assays. Using a simple fiber‐coupled USB‐spectrometer and 980 nm diode laser excitation in a 96‐well microplate, ratiometric FRET from UCNP‐to‐Cy3 can quantify miR20a in a 0.01–10 × 10 −9 m concentration range with a detection limit of 30 × 10 −12 m (4.5 fmol of miR20a), which is more than 20‐fold lower compared to quantum dot‐based FRET assays. The functional thin‐coating DNA‐UCNP nanohybrids have a strong potential for translating UCNPs into advanced DNA‐based biosensing, bioimaging, and high‐throughput and point‐of‐care clinical diagnostics. Abstract : DNA‐functionalized upconversion nanoparticles with thin and stable coatings are used for rapid and highly sensitive and selective quantification of a few femtomols of microRNA using single‐step Förster resonance energy transfer assays and a simple USB‐spectrometer detection platform.